Analisis Kebutuhan Daya Pada Perancangan Sistem Instrumentasi Smart Garden ISMOTA - Nursyaban, Ikhwan; Stefanie, Arnisa; Lammad, Ibrahim (Peneliti.net, 2024)
This study applies the method of calculating the power of each component before designing the implementation of the instrumentation system for monitoring ISMOTA orchid plants. The instrumentation system in this tool can monitor orchid plants by conditioning the temperature and humidity of the plant's soil. There is also a live stream mode because it uses the ESP32 Cam module. Temperature conditioning is carried out on the DHT22 sensor, conditioning plant moisture as input also from sensor readings carried out by the Soil Moisture sensor. the program module to process all existing inputs using ESP32. The output of this system is in the form of 3 types of actuators such as Fan Dc, Solenoid Valve and also Pump Dc. The system will work when the temperature reaches the normal threshold in the range of 21° - 29° to turn on the Dc Fan as a condition for the temperature around the plant. For humidity, system conditioning will be regulated with the output of the Pump Dc actuator and Selonoid Valve to water the plants so that conditions return to the humidity limit, which is at 80%.